Efficient and facile synthesis of novel stable monodeuterium labeled ractopamine. (2nd November 2015) - Su, Feifei; Wu, Fulong; Tang, He; Wang, Zhonghua; Wu, Fanhong
Abstract : A novel synthetic route to stable deuterium labeled ractopamine was disclosed with 6.49% total yield and 97.7% isotopic abundance. Its structure and the isotope‐abundance were confirmed according to 1 H‐NMR and high‐resolution mass spectrometry. Abstract : A novel synthetic route to stable deuterium labeled ractopamine was disclosed with 9 steps, 6.49% total yield and 97.7% isotopic abundance. Its structure and the isotope‐abundance were confirmed according to 1 H‐NMR and high‐resolution mass spectrometry.